Implementation of PSAK 221 on Foreign Currency Transactions of PT Adaro Andalan Indonesia Tbk - Fitra Izzadieny; Kristianto Tricahya Prabowo; Riyadatul Muthmainnah; Victorinus Laoli (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research discusses the implementation of PSAK 221, which regulates the impact of foreign exchange rate changes on the financial statements of PT Adaro Andalan Indonesia Tbk, particularly related to foreign currency transactions. PSAK 221 establishes the methods for recording and reporting foreign currency transactions and recognizing exchange rate differences arising from exchange rate fluctuations. In the context of PT Adaro, which operates in the mining sector and frequently conducts international transactions, implementing this standard is crucial to maintaining the accuracy and transparency of financial reports that stakeholders require. This research aims to guide PT Adaro in managing foreign currency transactions and recording the impact of exchange rate fluctuations by PSAK 221 provisions to ensure accurate, transparent, and compliant financial statements with applicable accounting standards. This research uses a qualitative descriptive method, with a document study approach, to analyze the annual financial statements of PT Adaro Andalan Indonesia Tbk. The data used consists of secondary data obtained from the company’s financial statements and foreign currency transaction records, covering 2024, to identify the application of PSAK 221 in foreign currency transactions and its impact on the financial statements.